Analisis Faktor-Faktor yang Berhubungan dengan Efektivitas Komunikasi Perawat dan Pasien di Ruang Rawat Inap Rumah Sakit Harapan Mulia Kabupaten Bekasi Tahun 2015 - Agustrianti, Prasetyaningtyas (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
The study aims to determine the factors associated with the effectiveness of nurse and patient communication atinpatient unit in Harapan Mulia Hospitallocated in Bekasi Regency.It is a quantitative study with cross-sectional design.Samples are the total population amounted to 30 nurses with 60 patients as respondentsconducted in March - May 2015. The results showed that 53.3% of patients perceived that nurses’s communication was effective, further analysis with logistic regression showed no significant relationship between the characters nurses, physical and mental fatigue, language, leadership and management support for hospitals, facilities and reward with the nurses and patients communication effectiveness.